QUANTITATIVE ESTIMATES OF THE PARAMETERS OF INTERACTION BETWEEN THE EARLY PROTEROZOIC PLUME AND LITHOSPHERE IN THE NORTHEASTERN BALTIC SHIELD - Filatova V.T. (My University, 2004)
The results of a numerical modeling carried out for physical substantiation of possible geodynamic settings during the formation of the Earth's crust in the northeastern Baltic Shield are presented. The available data on trends of the Early Proterozoic evolution of the northeastern Baltic Shield indicate an intraplate type of tectonic magmatic activity in the region during this period. Major geological and tectonic structures of the study region were mainly formed because of the ascent of the mantle plume and its subsequent active interaction with the lithospheric rocks, resulting in a wide spectrum of tectonomagmatic processes in the Earth's core. Analysis of the distribution of plutonic and volcanogenic formations, as well as of specific features of the evolution of rock components, revealed a complex character of their relationships related to alternating extension and compression regimes and the delivery of magmatic melts from sources located at different depths. We qualitatively estimated the parameters of the mantle plume that regulates the Early Proterozoic basic and ultrabasic rock magmatism in the region and constructed a general model of the nonlinear development of the crust-asthenosphere system in the lithospheric block.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой